The Effects of Parents’ Role and Learning Motivation Towards Vocabulary Mastery - Yuesi Setyorini (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2018)
This research aims at proving the effect of parents’ role partially towards vocabulary mastery, the effect of learning motivation partially towards vocabulary mastery, the effects of parents’s role and learning motivation simultaneously towards vocabulary mastery as well. The data is collected by using questionnaires technique and by conducting the vocabulary test. The sample consists of a number of grade XII students of three vocational high schools in Duren Sawit District East Jakarta in academic year 2012-2013. The data is analyzed by applying descriptive statistic analysis, correlation analysis and multiple regression analysis. The hypothesis is examined by conducting t-test and F-test. From the hypothesis test, it is gained that R2=0.804, F-test of parents’ role (X1) and learning motivation (X2) is 172.948. The multiple regression equation which is obtained is ? = 0.223 + 0.305 X1 + 0.479 X2. R2 = 0.804 indicates that both parents’ role (X1) and learning motivation (X2) collectively affect 80.4% upon vocabulary mastery, whereas the rests are the influences of another factors. The effect of parents’ role partially is significant because t observe > t table (5.792 > 1.67). The effect of learning motivation partially is significant because t observe> t table (11.168 > 1.67).